Model-based methods for improved maintainability and safety - Seshabhattaru, Vamsi (My University, 2011)
As technology improves by each passing day, so does its use in the automotive industry. Modern vehicles are designed with an increasing number of electronic components ranging from electronic control units, sensors and actuators, anti-lock breaking systems, and a host of other applications, increasing the complexity of the overall system. Reliability, safety and maintainability are among the three main areas of importance that need to be considered when designing electrical systems for road vehicles. The various methods implemented for system analysis also need to be updated on a regular basis as the complexity of the electrical systems implemented is ever increasing. One of the methods which is fast gaining importance is the model-based approach for system analysis. Model-based methods provide an easier way of system analysis through visual representations of physical components. Model-based methods are used for simulating, in a visual way, the desired behaviour of the electrical systems as well as the failure behaviour of the electrical systems. This master thesis mainly investigated the use of the model-based system-reasoning tool RODON during early design phases for system analysis. The thesis work has special focus on the usage of RODON tool for FMEA analysis and generation of diagnostic requirements, which need to be implemented in the target system. The capabilities of the RODON tool for doing reliability analysis have also been investigated. Different models with varying levels and techniques were developed to explore the results that can be achieved from the tool. A comparative analysis of the reliability analysis results achieved through the tool-based approach was compared to the results achieved through manual based methods. The use of RODON for various system analysis methods suggested in the upcoming functional safety standard ISO26262 was also explored.
Keywords: Information Technology; Informationsteknik